Biochar addition into activated sludge mitigate antibiotic toxicity on nitrification performance. (December 2021) - Kim, Youngjun; Oh, Seungdae
Abstract: This work examined the effects of biochar (BC) and a plastic carrier (PC) on nitrification of activated sludge (AS) in the presence of antibiotic ciprofloxacin (CIP). It was found that 5 mg/L CIP significantly inhibited both ammonium and nitrite oxidation by >75%. While the addition of PC into a reactor showed no effects on the fate of CIP, the addition of BC substantially decreased CIP concentrations in the reactor, thereby significantly reducing the CIP-mediated inhibition on the nitrification performance. 16S rRNA gene-based community profiling revealed a significant change in the structure of the nitrifying community in the presence of CIP. While Nitrosomonas oligotropha and Nitrospira sp. were significantly inhibited by CIP, they recovered with the BC addition. Batch experiments were performed to determine removal routes of CIP in the BC-dosed reactor. While no significant removal of CIP occurred via abiotic routes such as volatilization, photolysis, and hydrolysis, CIP was removed primarily by adsorption to BC and co-metabolic biodegradation by the nitrifying community. The first-order removal rate constant of CIP was 0.63 d −1 in the nitrifying condition, which was increased to 0.86 d −1 with the BC addition. Overall, this study suggests that BC can be a promising additive into environmental bioprocesses for mitigating antibiotic toxicity and enhancing nutrient removal performance in the presence of high antibiotic loads. Highlights: CIP inhibits Nitrosomonas oligotropha and Nitrospira responsible for nitritation and nitratation, respectively. Adding BC recovers both nitrification performance and the CIP-sensitive nitrifiers. Mechanisms controlling the fate and the toxicity of CIP in the BC-dosed reactor are elucidated. BC can be a promising additive for enhancing the removal of nitrogen and micropollutants.